Semi-conducting mixed-valent X4TCNQI−/II− (X = H, F) charge-transfer complexes with C6H2(NH2)4. Issue 27 (23rd June 2020) - Sutton, Ashley L.; Abrahams, Brendan F.; D'Alessandro, Deanna M.; Goerigk, Lars; Hudson, Timothy A.; Robson, Richard; Usov, Pavel M.
Abstract : A pair of semi-conducting, charge transfer complexes of composition, [C6 H2 (NH2 )4 ][TCNQ] and [C6 H2 (NH2 )4 ][F4 TCNQ] is described in which the TCNQ and F4 TCNQ species each exhibit a -I/-II mixed-valent state. Abstract : We report further characterisation on the previously described [C6 H2 (NH2 )4 ][TCNQ] charge-transfer (CT) complex. An in-depth analysis of the crystallographic data aided by spectroscopic methods indicates the compound is mixed-valent with TCNQ I−/II− species. The analogous F4 TCNQ CT complex has been synthesised and spectroscopic methods suggest that [C6 H2 (NH2 )4 ][F4 TCNQ] is also mixed-valent. Electrical conductivity measurements on both complexes indicate semi-conductor behaviour, with [C6 H2 (NH2 )4 ][TCNQ] exhibiting a σ 300K = 9.8 × 10 −4 S cm −1 and an E a = 0.10(1) eV. Density functional theory studies on both CT complexes reveal band structures suggestive of ambipolar transport, with a super-exchange mechanism.